Модель забезпечення цілісності інформаційних об'єктів із застосуванням узагальненого завадостійкого коду умовних лишків - Василенко, С.В. (Моделювання та інформаційні технології, 2010)
Explored possibilities of the use in the networks of
telecommunication of model of providing of integrity of information holding object on
the base of the generalized antigambling code of conditional tailings. In the article of
such realizable analysis of his possibilities.